Β-Carboline-directed decarboxylative acylation of ortho-C(sp2)–H of the aryl ring of aryl(β-carbolin-1-yl)methanones with α-ketoacids under palladium catalysis12. Issue 56 (24th May 2016) - Kolle, Shivalinga; Batra, Sanjay
Abstract : A Pd-catalysed β-carboline assisted decarboxylative acylation of ortho -C(sp 2 )–H of aryl ring of aryl(β-carbolin-1-yl)methanones using α-oxocarboxylic acid as the acyl ion source to form (2-aroylaryl)(β-carbolin-2-yl)methanones is demonstrated. Abstract : A palladium-catalysed β-carboline directed decarboxylative acylation of ortho -C(sp 2 )–H of the aryl ring of aryl(β-carbolin-1-yl)methanones using α-oxocarboxylic acid as the acyl ion equivalent to form (2-aroylaryl)(β-carbolin-2-yl)methanones is described. The utility of these products for preparing β-carboline-tethered phthalazine systems is also demonstrated.